ANALISIS KUALITAS INFORMASI AKUNTANSI MELALUI PENDEKATAN TEORI INSTITUSIONAL ISOMORFISME - Dwi Winarni; Luthfi Zamakhsyari (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2021)
Changes to a system within the organization are carried out simply to get recognition or awards rather than to improve performance substantively. Performance reports that have been made by government agencies are only meant to fulfill regulatory and regulatory requirements and do not reflect the performance that occurs in the field. This study examines and analyzes how local governments improve the quality of accounting information in terms of institutional isomorphism theory. The research method used is a qualitative method so that it can explore and understand the data in more depth. The local government in Indonesia was chosen as the object of research because it has a characteristic in the current application of New Public Management (NPM). The analysis was carried out using three indicators that describe institutional isomorphism (coercive, mimetic, and normative). The results show that regulation, management commitment, and human resource competence have a positive impact on the implementation of the preparation of financial statements according to standards and the quality of accounting information produced.